The Balance between Hydrophobicity/Aromaticity and Positively Charged Residues May Influence the Cell Penetration Ability - Dóra Soltész; Ildikó Szabó; Zoltán Bánóczi (Pharmaceutics, 2023)
Cell-penetrating peptides (CPPs) are commonly modified to increase their cellular uptake, alter the mechanism of penetration or enhance their endosomal release. Earlier, we described the internalization enhancement ability of the 4-((4-(dimethylamino)phenyl)azo)benzoyl (Dabcyl) group. We proved that this modification on the N-terminus of tetra- and hexaarginine enhanced their cellular uptake. The introduction of an aromatic ring 4-(aminomethyl) benzoic acid, AMBA) into the peptide backbone has a synergistic effect with Dabcyl, and the tetraarginine derivatives had outstanding cellular uptake. Based on these results, the effect of Dabcyl or Dabcyl-AMBA modification on the internalization of oligoarginines was studied. Oligoarginines were modified with these groups and their internalization was measured using flow cytometry. The concentration dependence of the cellular uptake of selected constructs was compared too. Their internalization mechanism was also examined by using different endocytosis inhibitors. While the effect of the Dabcyl group was optimal for hexaarginine, the Dabcyl-AMBA group increased the cellular uptake in the case of all oligoarginines. All derivatives, with the exception of only tetraarginine, were more effective than the octaarginine control. The internalization mechanism was dependent on the size of the oligoarginine and was independent of the modification. Our findings suggest that these modifications enhanced the internalization of oligoarginines and resulted in novel, very effective CPPs.